Proteomics Characterization of the Secretome from Rat Pancreatic Stellate Cells with ATP-Binding Cassette Transporters (ABCG2) and NCAM Phenotype. (31st October 2013) - Lucas, Maria; Mato, Eugenia; Barceló-Batllori, Silvia; Gomis, Ramon; Novials, Anna
Abstract : We have previously reported the identification of a pancreata mitoxantrone-resistant cell population which expressed the ABCG2 transporter with a pancreatic stellate cells phenotype (PaSC) and ability of secreting insulin after inducing their differentiation. The characterization of the secretome of this cell population by two-dimensional electrophoresis (2D) coupled with mass spectrometry MALDI-TOF was able to identify seventy-six protein spots involved in different cellular processes: development/differentiation, proteases, immune response, and other. Moreover, Ingenuity Pathway Analysis displayed several significant networks and TGF β 1 molecule was identified as a central node of one of them. The effect of this active molecule secreted in the conditioned medium was investigated in ductal cell line (ARIP). The results showed that the conditioned medium inhibited their proliferation without affecting their cell viability. Additionally, they showed an upregulation of PDX1 and downregulation of CK19. The rate of ARIP cell proliferation was recovered, but no effects on the gene expression were observed after using TGF β 1-neutralising antibody. Proteins associated with cell growth, development and differentiation such as PEDF, LIF, and Wnt5b, identified in the secretome, could be involved in the observed transcription changes. These finding may suggest a new paracrine action of PaSCs involved in the proliferation and differentiation pathways not yet identified.